Prevalence and Risk Factors Associated with Chronic Diseases Among Young Adult in Bangladesh - Hasan, M. N. (Journal of Scientific Research, 2023)
One of the major health challenges of the century is the prevalence of chronic diseases in young adults. The aim of the study was to identify the risk factors for chronic disease and the prevalence of chronic disease in individuals aged 18 to 39. The outcome variable was chronic diseases, and potential predictors included sex, age, education, work status, division, region, smoking status, and respondent's income. Of the 5490 young people, 1782 (32.5 %) had at least one chronic illness. Age, work status, division, geography, and smoking status were significant predictors of chronic illnesses in the multivariate model. Compared to younger young adults, those aged 30-39 had greater odds of developing chronic diseases (OR = 1.57, 95 % CI: 1.16–2.13). Residents in socioeconomically disadvantaged areas are more likely to have chronic illnesses than their more affluent counterparts. Young men are more likely than women to experience chronic illness (OR = 1.06, 95 % CI: 0.92-1.21), although this difference wasn't statistically significant. The highly educated group reports chronic disease more frequently than other groups. These findings, particularly those pertaining to decision-makers, can aid in the justification, direction, and support of programs required to address these altering epidemiological trends.